Analisis Spasial Sebaran Kasus Tuberkulosis Paru Ditinjau Dari Faktor Lingkungan Dalam dan Luar Rumah di Kabupaten PekalonganAnalisis Spasial Sebaran Kasus Tuberkulosis Paru Ditinjau Dari Faktor Lingkungan Dalam dan Luar Rumah di Kabupaten Pekalongan - Bambang Ruswanto; Nurjazuli Nurjazuli; Mursid Raharjo (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Pulmonary tuberculosis (TB) is caused by “mycobacterium tuberculosis”. In Pekalongan, the prevalence rate of TB is 1,08 per 1000 population. Approximately 75% of those is the economically productive group. No information of TB distribution based on the environmental characteristic. This research aimed to anlyze the association between demographic, physical environment factors and to conduct spatial analysis of regional characteristics that influence the distribution of tuberculosis cases in Pekalongan Regency. Method: It was an observasional research using case control design. Data analysis performed by chi-square (univariate and bivariate analysis). Multivariate analysis uses logistic regression test to determine of risk factors which the association is significant with pulmonary tuberculosis. Result : The statistical test showed that occupancy density, ventilation area, humidity of room in the house, air temperature, natural lighting in the house, kind of floor, air temperature outside the house, knowledge, nutrition status, and contact with the cases (p=0,05). While the result of multivariate analysis proved that there are seven factors which have significantly association with tuberculosis: knowledge, occupancy density, temperature in the home, natural lighting in the house, kind of floor, nutrition status, and contact with cases (OR>1,00). It was recommended to improve thr physical environment of the house, increase investigation and counselling for amily contact in the same house. Keywords: Risk factors, Pulmonary tuberculosis, Spatial analysis